Depressive symptoms across the menopause transition: findings from a large population-based cohort study. Issue 12 (December 2016) - Hickey, Martha; Schoenaker, Danielle A.J.M.; Joffe, Hadine; Mishra, Gita D.
Abstract: Objective: The aim of the study was to describe the trajectories of depressive symptoms in a large population-based cohort of midaged women, and to examine the associations of current and changing reproductive stage with depressive symptoms over time. Methods: Prospective, population-based cohort study of 13, 715 women aged 45 to 50 years followed up for over 15 years (Australian Longitudinal Study on Women's Health). Nearly 6, 000 women provided complete data for this study. Menopause status was determined from questionnaires about hysterectomy, oophorectomy, hormone therapy, and menstrual patterns. Depressive symptoms were measured using the Center for Epidemiologic Studies Depression scale (CESD-10). Results: Latent class analysis indicated four distinct profiles of CESD-10 scores over 15 years: stable low (80.0%), increasing (9.0%), decreasing (8.5%), and stable high (2.5%). Those with "increasing" depressive symptoms were more likely to have had bilateral salpingo-oophorectomy or be perimenopausal at baseline compared with women in the "stable low" group. Depressive symptoms were higher in perimenopausal women, (higher CESD-10 score of 0.19, 95% CI 0.02, 0.31), after hysterectomy alone (0.53, 95% CI 0.31, 0.74), bilateral salpingo-oophorectomy with/without hysterectomy (0.85, 95% CI 0.58, 1.12), hormone therapy users (0.19, 95% CI 0.01, 0.36), and after starting or stopping hormone therapy compared with postmenopausal women (adjusted for sociodemographic factors, vasomotor symptoms, health behaviors, and history of depression diagnosis or treatment). Conclusions: Depressive symptoms follow distinct trajectories across the menopause transition. Most women have stable symptoms, but around 9% have increasing symptoms and a similar proportion (8.5%) decreasing symptoms. Increasing depressive symptoms were independent of vasomotor symptoms but were associated with oophorectomy and stopping or starting hormone therapy. A large number of women were excluded due to missing data, and thus the results should be interpreted with caution.